Current opinions concerning the restoration of endodontically treated teeth: basic principles - VȦrlan, C (Carol Davila University Press, 2009)
The goal of this general article is to present a survey of the current knowledge about the clinical approach of restoring endodontically treated teeth. The best way to restore teeth after root canal treatment has long been and still is a controversial subject of debate to this day. The clinical approach of restoring endodontically treated teeth needs taking into consideration several issues: aims of coronal restoration, criteria for establishing the various modalities of coronal restoration, clinical solutions of restoring teeth after endodontic treatment, guidelines regarding restorative materials and techniques, possibilities and limits of restoration using direct adhesive materials and techniques. The aims of coronal restoration of endodontically treated teeth are generally considered to be the following ones: to prevent recontamination of the root canal system and / or periapical space, to replace missing hard dental tissues and to restore coronal morphology and functions, to provide the necessary strength for the restoration/tooth complex in order to withstand functional stress and prevent crown and/or root fracture. The criteria for establishing the modalities of coronal restoration for endodontically treated teeth are: amount and quality of remaining hard dental tissues, topography and coronal morphology of the tooth, functional occlusal forces that the restoration/tooth complex has to withstand, restoring requirements in order to include the treated tooth in a comprehensive oral rehabilitation treatment plan, esthetic requirements.